Investigating the mediating effect of affective commitment on the link between work attitude and employee performance - Melda Aulia Ramadhani; Nita Priska Ambarita; Muhammad Rinaldi (Trigin Publisher, 2025)
This study aims to examine the influence of work attitude on employee performance, with affective commitment as a mediating variable, in the context of private-sector companies in Indonesia. Using a quantitative explanatory approach, data were collected from 100 employees through a structured questionnaire. The results indicate that work attitude significantly affects affective commitment but does not directly influence employee performance. Furthermore, affective commitment also does not have a significant effect on performance and does not mediate the relationship between work attitude and performance. These findings suggest that while a positive work attitude can foster emotional attachment to the organization, it does not necessarily lead to improved performance outcomes. Organizational performance improvements may require additional supporting factors such as job clarity, incentives, and leadership support. This study contributes to the understanding of psychological and behavioral dynamics in Indonesian workplaces and highlights the need for holistic HR strategies that combine attitudinal, structural, and motivational elements.